2015
DOI: 10.3928/01477447-20150902-62
|View full text |Cite
|
Sign up to set email alerts
|

Management of Humeral Shaft Fractures With Intramedullary Interlocking Nail Versus Locking Compression Plate

Abstract: Surgical fixation of humeral shaft fractures generally involves plating or nailing. It is unclear whether one method is more effective than the other. The aim of this study was to compare the results of the intramedullary nail and locking compression plate for the treatment of humeral shaft fractures. A total of 60 patients with humeral shaft fractures were randomized to undergo surgery with an intramedullary interlocking nail (n=30) or locking compression plate (n=30). The outcome was assessed in terms of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 35 publications
5
45
1
Order By: Relevance
“…4 We also report interlocking nailing is superior to plating as nailing has higher rate of union and earlier union with lower incidence of complications in comparison to the conventional plate osteosynthesis for diaphyseal fractures of humerus. Various studies have reported different outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 We also report interlocking nailing is superior to plating as nailing has higher rate of union and earlier union with lower incidence of complications in comparison to the conventional plate osteosynthesis for diaphyseal fractures of humerus. Various studies have reported different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…10 Comparative studies of plate osteosynthesis versus intramedullary nailing in fractures of shaft of humerus have reported contradictory conclusions. 1,3,4,6,8,11,12 The purpose of this study was to compare nailing and plating in humeral shaft fractures with regard to union rate, time taken for fracture union, functional outcome and incidence of complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is comparable to the union rate achieved by Crates (94.5%), Fan (96.7%), Chapman (87%), Tsourvakas, (95.8%), Petsatodes (92.3%). 6,13,18,22,23 Reported nonunion rate in recent literature is 0-8%. 17 In our series, 2 patients had non-union.…”
Section: Discussionmentioning
confidence: 99%
“…Recently many authors in prospective randomized studies, comparing IMN versus locking compression plates in treatment of humeral Shaft Fracture found intraoperative blood loss, operative time, hospital stay and average union time) were significantly lower in patients treated with IMN and no significant difference between the two groups in terms of union rate, shoulder function or complications. [13][14][15][16][17] Shoulder pain and restriction of shoulder movements and risk of delayed union have been suggested as disadvantages of antegrade intramedullary fixation. [18][19][20] Impairment of shoulder function with antegrade IMN could be due to rotator cuff violation, and subacromial impingement.…”
Section: Discussionmentioning
confidence: 99%